Increased expression of miR-27 predicts poor prognosis and promotes tumorigenesis in human multiple myeloma. Issue 4 (9th April 2019) - Che, Feifei; Wan, Chunqian; Dai, Jingying; Chen, Jiao
Abstract : Multiple myeloma (MM) is an incurable hematological malignancy characterized by abnormal infiltration of plasma cells in the bone marrow. MicroRNAs (miRNAs) have emerged as crucial regulators in human tumorigenesis and tumor progression. miR-27, a novel cancer-related miRNA, has been confirmed to be implicated in multiple types of human tumors; however, its biological role in MM remains largely unknown. The present study aimed to characterize the biological role of miR-27 in MM and elucidate the potential molecular mechanisms. Here we found that miR-27 was significantly up-regulated in MM samples compared with normal bone marrow samples from healthy donors. Moreover, the log-rank test and Kaplan–Meier survival analysis displayed that MM patients with high miR-27 expression experienced a significantly shorter overall survival than those with low miR-27 expression. In the current study, we transfected MM cells with miR-27 mimics or miR-27 inhibitor to manipulate its expression. Functional studies demonstrated that miR-27 overexpression promoted MM cell proliferation, facilitated cell cycle progression, and expedited cell migration and invasion; whereas miR-27 knockdown inhibited cell proliferation, induced cell cycle arrest, and slowed down cell motility. Mechanistic studies revealed that Sprouty homolog 2 (SPRY2) was a direct target of miR-27 and that rescuing SPRY2 expression reversed the promoting effects of miR-27 on MM cell proliferation, migration, and invasion. Besides, miR-27 ablation suppressed tumorigenecity of MM cells in mouse xenograft models. Collectively, our data indicate that miR-27 exerts its oncogenic functions in MM by targetting SPRY2 and that miR-27 may be used as a promising candidate target in MM treatment.